Negative consequences of hyperization of the function of the natural environment as a place of accumulation or disposal of human waste - Zachepylo, Mykyta; Garkava, Kateryna; Kosoholova, Liudmyla; Baranovskyy, Mikhaylo; Kuznietsova, Olena; Monchenko, Olena; Kuz, Tetiana (Problems of Environmental Biotechnology, 2024)
The author analyzes the negative consequences of hyperinflation of the function of the natural environment as a place of accumulation or disposal of human waste